“Heavy metals concentration (cr total, pb, cd) in surface water and sediments in the salado (guayaquil)” - Alcivar, Mariana de Jesús Alcivar; Lastenia Mosquera, Jessica (Revista Universidad de Guayaquil, 2012)
This work done during the dry season (August, September, October) of 2010 at five points of Estero Salado de Guayaquil was determined the concentration of heavy metals Cadmium (Cd), total chromium (Cr), Lead (Pb) in the surface water and sediment matrices the same as reported values of Cd (ND - 0.06 ppm), Cr and Pb (ND - 0.01 ppm) for surface water samples, while sediments were Cd (ND - 9 50), Cr (11, 99 to 43.47 ppm), Pb (13.47 to 69.47). In addition, samples of gastropods (Cerithidea validated) to determine whether these metals affect these organizations and therefore the food chain, organisms were captured in the study area in the month of October getting results of Cd (1.37 - 3 5), Cr (4.50 to 7.99), Pb (18.73 to 41.03). The values found in each of the matrices we reflect the environmental problems existing in this ecosystem due mainly to industrial activities, rapid population growth, deforestation and mismanagement of waste and discharges of domestic and industrial use untreated well causing deterioration of this ecosystem.
Keywords: Estero Salado; heavy metals; gastropods; environment; ecosystem